Recent Developments in Braiding and Narrow Weaving - Kyosev, Yordan (Springer International Publishing : Imprint: Springer, 2016)
This book discusses the latest developments in narrow fabrics from research institutions, machinery building companies and producers of such products, presented during the International Week of Narrow Fabrics in March 2016 in Mönchengladbach, Germany. It also demonstrates different applications of braided and woven fabrics. Braided and woven narrow products are produced using completely different techniques, but have a lot of similarities in their applications - they are used as belts, ropes and tubes in areas ranging from medical textiles, cables, technical and home applications to large-scale transport belts and long tubes for transporting oil from the bottom of the ocean.